Worker Centers, Worker Center Networks, and the Promise of Protections for Low‐Wage Workers. Issue 1 (March 2015) - Cordero‐Guzmán, Héctor R.
Abstract : Over the last two decades, a number of community‐based and community‐led organizations—known as worker centers—have been engaging in organizing, research, direct service provision, policy analysis and development, and advocacy with low‐wage workers in the most marginalized sectors of the labor market. Worker centers and worker center networks engage in a broad range of labor market activities, including worker‐based programs, services, and campaigns; labor market intermediation; employer‐focused strategies; and a range of consumer and community education and engagement campaigns and initiatives. Worker centers and worker center networks play an essential role in low‐wage labor markets by identifying key sectors in the low‐wage economy where there are large numbers of vulnerable workers and labor violations; by organizing workers, developing and managing campaigns, and providing access to legal remedies for labor violations; and by developing strategies to improve pay, working conditions, and other aspects of job quality in low‐wage occupations. Any strategy designed to reduce labor violations and improve working conditions for low‐wage workers should take into account the functions and roles of worker centers and worker center networks in articulating the needs of workers and devising strategies, programs, campaigns, and initiatives designed to address them.